POLA ASUH DENGAN KEJADIAN STUNTING PADA BALITA DI KABUPATEN POLEWALI MANDAR - Yudianti Yudianti; Rahmat Haji Saeni (Jurnal Kesehatan Manarang, 2016)
Stunting is a condition which indicated by chronic growth inhibition and caused by long-term malnutrition. In Tinambung district has 50.9% stunting cases. Stunting in children caused by several factors related among parenting. The objective of this study is to know association parenting consists of feeding practices, hygiene practices and seeking treatment practices in infants. This study was observational case control study with 51 stunting toddlers samples and 51 toddlers normal by systematic random sampling. The independent variables consist of feeding practices, hygiene practices and health seeking practices while the dependent variable is toddler who suffered stunting. Statistical analysis by bivariate with Chi Square test. There is association between feeding practices, personal hygiene practice with incidence of stunting toddlers. There is no association between seeking treatment practices with of stunting toddlers